The application of organic mulch and chicken manure for improving soil water availability and yield of turmeric (Curcuma domestica Val) in an Inceptisol of Jambi, Indonesia - Sunarti; Lizawati (Brawijaya University, 2024)
Turmeric (Curcuma domestica Val) is one of the agricultural commodities being developed by the Jambi Province of Indonesia. However, despite the high value of turmeric, its productivity in Jambi Province is low. This is because the crop is mostly cultivated in marginal lands dominated by Inceptisol, which has low fertility and low water availability. Organic mulch and chicken manure have the potential to be used to improve soil water availability and crop yield. This research aimed to evaluate the effect of organic mulch cover and chicken manure on soil water availability and turmeric yield. The treatments tested were combinations of various percentages of organic mulch cover (30%, 60%, and 90%, and chicken manure dosage (0, 5, 10, and 15 t ha-1). The twelve treatment combinations were arranged in a randomized block design with three replications. The results showed that the combination of the percentage of organic mulch cover and chicken manure dosage affected soil organic matter content, soil bulk density, soil pore size distribution, soil water availability, and turmeric yield. The application of 30% cover of organic mulch and 10 t ha-1 of chicken manure was found to be the best combination to improve soil available water and turmeric yield. The regression analysis results showed that soil bulk density, organic carbon, fast-drainage pores, and slow-drainage pores simultaneously affected the soil water content, with an R2 value of 0.85. The results of this study proved that soil available water is also closely correlated with turmeric yield.